Sustainable household waste management improvement in Dhaka city, Bangladesh - Rafia, Afroz (Inderscience Publisher, 2011)
The objective of this study is to conduct an economic study to identify the factors which affect households’ solid waste generation,households’ willingness to pay to improve the solid waste management and households’ recycling behaviour in Dhaka City. The results showed that the waste generation of the households in Dhaka City was significantly affected by household size, income and concern about the environment. The results showed that the aggregate value of WTP of the respondents in Dhaka City was 7.6 million Taka (USD 0.1 million). Another logistic regression model was used to identify the factors which affect households’ recycling behaviour. The results showed that environmental consciousness, the availability of storage space, and age (25 to 35), are significant positive predictors of recycling behaviour. Another variable INCOME 2 (TK3,000 to TK15,000) is also positively correlated with recycling.